Is it as simple as run more, win more? Influence of running load on match outcome and final league position across nine consecutive English Premier League football seasons - Allen, T.; Taberner, M.; Zhilkin, M.; Alexander, J.; Harper, D.; Rhodes, D. (International Journal of Sports Science & Coaching, 2025)
Purpose This study aimed to assess the relationship between running load trends, between teams in a match, match outcomes, and final league positions in the English Premier League (EPL) from 2015/16 to 2023/24 using semi-automated optical tracking systems.